A new simple UV-Vis spectrophotometric method for determination of sulfite species in vegetables and dried fruits using a preconcentration process. Issue 2 (1st December 2015) - Altunay, Nail; Gürkan, Ramazan
Abstract : Ultrasonic assisted CPE was used for the preconcentration of sulfite. The effect of foreign ions which may be present in actual samples was investigated. The method was applied to the quantification of sulfite in vegetables and dried fruits. The analytical variables affecting UA-CPE efficiency were optimized. The enrichment factor 95 was obtained. Abstract : A new eco-friendly, selective and sensitive method was developed for preconcentration and determination of trace levels of sulfite by ultrasonic-assisted cloud point extraction (UA-CPE). The method is based on the selective ion-association of the anionic complex, Cu(SO3 )2 2−, produced depending on sulfite concentration in the presence of excess Cu(ii ) ions with toluidine blue (TB + ) at pH 7.5, and then extraction of the formed ion-associate complex into the surfactant rich phase of Triton X-45 micelles. Under the optimized reagent conditions, the calibration curve is linear in range of 2.5–350 μg L −1, and the limits of detection and quantification of the method (LOD and LOQ) (3 σ blank / m and 10 σ blank / m ) are 1.15 and 3.82 μg L −1 with a sensitivity enhancement factor of 95. The results demonstrated that the method achieved acceptable quantitative recoveries of 95.7–102.9% with relative standard deviations (RSDs) of 2.1–4.8%. The method showed good selectivity, and was successfully applied to the quantification of sulfite species in vegetable and dried fruit samples with satisfactory results. The results were compared with those of the standard 5, 5′-dithio-bis(2-nitrobenzoic acid) (DTNB) method, and the two paired t -test was used to determine whether the results obtained by the two methods differ significantly.